Lignocellulose-Chitosan-Multiwalled Carbon Nanotube Composites with Improved Mechanical Strength, Dimensional Stability and Fire Retardancy - Wang, Zhe (Polymers (Basel), 2018)
A novel composite composed of lignocellulose (LC), glutaraldehyde crosslinked chitosan (GC) and multiwalled carbon nanotube (MWCNT) was fabricated by the hot-pressing process. The effect of the additional GC and MWCNT on the mechanical strength, dimensional stability and fire retardancy of lignocellulose composites was investigated. The results showed that LC/GC/MWCNT composite exhibited the maximum modulus of rupture (MOR) of 35.3 MPa, modulus of elasticity (MOE) of 2789.1 MPa and internal bonding (IB) strength of 1.2 MPa. Meanwhile, the LC/GC/MWCNT composite displayed improved dimensional stability with a thickness swelling (TS) value of 22.4%. Besides, the LC/GC/MWCNT composite exhibited improved fire retardancy with a limiting oxygen index of 29.0%. The peak heat release rate, the total heat release, the total smoke production and the maximum smoke production ratio of LC/GC/MWCNT composite decreased by 15.9%, 10.7%, 45.5% and 20.7% compared with those of LC composite, respectively. Therefore, the LC/GC/MWCNT composite may be a promising candidate for green wood based composites.